Menopausal experience among postmenopausal women in Kuantan,Pahang—a qualitative study - Jamani, Nurjasmine Aida; Mohamad Ishak, Nurul Najmi; Abdul Hadi, Azwanis; Abd. Aziz, Karimah Hanim; Mohd Ariffin, Siti Roshaidai (2019)
* Menopause signifies the beginning of a non-reproductive phase from the reproductive period. * Menopausal experiences and symptoms vary across the cultures and countries. * It is very imperative to understand how menopause both enriches and challenges women’s lives.